State regulation of public libraries in Russia in the first half of the XIX century - D. I. Popov (Омский научный вестник: Серия "Общество. История. Современность")
The article reveals the content of state regulation of the activities of public libraries in Russia in the first half of the 19th century. It is shown that the government showed interest in involving the public in the development of the cultural life of urban centers, and therefore created relatively comfortable legal conditions and an organizational environment for the work of public libraries. In the 1830, the authorities tried, using bureaucratic methods, to introduce a public initiative to create public libraries in provincial cities. In response to the proposal of the head of the Free Economic Society P. S. Mordvinova, the Minister of Internal Affairs attracted the heads of regions — governors — to create a kind of library partnership. Local authorities, for their part, had to guarantee legal status to provincial libraries, provide them with organizational assistance, and representatives of the public, for their part, had to accept funding and carry out ongoing library work. The government established a licensing procedure for opening public libraries, which received legal status and the ability to independently stock book depositories. In an effort to prevent public libraries from becoming centers of anti-government propaganda, the authorities exercised administrative and police supervision over them. The results of the implementation of the ministerial project turned out to be modest: instead of the planned fifty-two, only twenty-nine public libraries were opened, most of which ceased to exist within 10–15 years. However, the general principles of state regulation of the activities of provincial libraries were extended to all other public libraries in Russia. In the middle of the 19th century, a library boom began in the country, which was caused by numerous public initiatives from below